Effects of adjuvants in a rabies-vectored Ebola virus vaccine on protection from surrogate challenge - Catherine Yankowski; Drishya Kurup; Christoph Wirblich; Matthias J. Schnell (npj Vaccines, 2023)
Abstract Ebola virus is the primary contributor to the global threat of filovirus severe hemorrhagic fever, and Ebola virus disease has a case fatality rate of 50–90%. An inactivated, bivalent filovirus/rabies virus vaccine, FILORAB1, consists of recombinant rabies virus virions expressing the Ebola virus glycoprotein. FILORAB1 is immunogenic and protective from Ebola virus challenge in mice and non-human primates, and protection is enhanced when formulated with toll-like receptor 4 agonist Glucopyranosyl lipid adjuvant (GLA) in a squalene oil-in-water emulsion (SE). Through an adjuvant comparison in mice, we demonstrate that GLA-SE improves FILORAB1 efficacy by activating the innate immune system and shaping a Th1-biased adaptive immune response. GLA-SE adjuvanted mice and those adjuvanted with the SE component are better protected from surrogate challenge, while Th2 alum adjuvanted mice are not. Additionally, the immune response to FILORAB1 is long-lasting, as exhibited by highly-maintained serum antibody titers and long-lived cells in the spleen and bone marrow.